Penerapan Metode Weighted Aggregated Sum Product Assesment Pada Seleksi Calon Paskibra - Sunyoto (Buletin Ilmiah Informatika Teknologi, 2023)
Paskibra or better known as the Flag Raising Troop is a troop tasked with raising the heritage flag at the ceremony commemorating the proclamation of Indonesian independence on 17 August. Paskibra members are selected through a selection process that is held every year. Therefore we need a decision support system that can provide convenience in assisting the school in selecting candidates for paskibra at SMK N1 Kualuh Hilir. This research suggests a decision support system that can assist in the selection of prospective paskibra using the Weighted Aggregated Sum Product Assessment (WASPAS) method. The WASPAS method is a component of the supporting system, the WASPAS method for making decisions from each alternative, then each of these alternatives has several criteria that are used as a reference in calculations with the Waspas method. The WASPAS method used for ranking values, using this ranking method is expected in the selection of Paskibra candidates to be more precise because it is based on the value of distinction and weight that has been determined so that maximum results will be obtained